Poesia concreta e mídia digital: o caso Augusto de Campos - Carvalho, Audrei Aparecida Franco de (2007)
The dialog between Augusto de Campos work and available medias in each period, it is de start point for this research. This affirmation suggests the investigation about poetic procedures put in practice by Augusto de Campos at the possibility of translation to electronic-digital support. The work hypothesis are: a) Augusto de Campos poetry is intersemiotic; b) the intersemiotic features of Augusto de Campos poetry, always connected at new media technologies, presume unexpected concepts of translation and poetry; c) these features presume a translation in constant process. The theorical and methodological foundations are divided in three parts: the concrete poetry and Augusto de Campos poetry will be analysed through the critical studies about concrete poetry, that was done by the concrete poets in: Teoria da Poesia Concreta (1987). The second part is formed by studies of the procedures used to the translation of concrete poems to digital media, it was found at: Ertho Albino de Souza, Ricardo Araújo, Julio Plaza, Melo e Castro s work. The last part of this research is formed by the translation of poetamenos poems (1953) to digital media, they are: poetamenos, paraíso pudendo, lygia fingers, nossos dias com cimento, eis os amantes and dias dias dias. The selection of these poems isn t by chance. Since the 1950 s, Augusto de Campos indicated the need of using new medias in the artistic development: Mas luminosos, ou filmletras, quem os tivera! The translation practice from this research appeals to Julio Plaza s studies in: Tradução Intersemiótica (1987) and Processos criativos com os meios eletrônicos: poéticas digitais (1998). Besides, we use the Walter Benjamin s critical study: A Tarefa do Tradutor (1923), and Haroldo de Campos studies about creative translation, with these studies we intent to understand how a creative text reacts at a translation to another support. This research is important to Communication Studies because it brings the light to the relation among art, communication and technology, they are currently at Augusto de Campos work. The relation among these fields happens by the incorporation of elements and procedures found in the press, magazines, bright displays, Internet, and other places. It s important to remember the relationship between Brazilian concrete poetry and artistic moviments found all over the world. The conclusions achieved show the existence of the relation between Augusto de Campos poetry and electronic poetry. We notice, for example, the concern of both with the receiver, the moviment, the connection between image and sound, etc